Analysing Dewey's vocational aspects of education and Maslow's theory of motivation in support of vocational education and training - Elijah Takyi Mensah; Mingkun Chen; Seth Yeboah Ntim; Antoinette Gabrah (Springer, 2023)
Abstract Aim The aim of this article is to analyse Dewey's writing on vocational aspects of education in his book Democracy and Education: An introduction to the philosophy of education to identify and to relate the main philosophical ideas to Maslow's theory of motivation and to establish the key similarities between the two theories to support contemporary Vocational Education and Training. Concept. The paper used content analysis to identify key themes from Dewey's vocational aspect of education and synthesised them with Maslow's theory of motivation. Based on both theories the article describes how motivation is critical in people's pursuit of vocational career goals. Result The study identified source of livelihood, sustainable livelihood, social recognition, social contributions, academic, and career progression from Dewey's vocational aspect of education as key ideas that are like Maslow's physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization needs that influence people's choice in vocational career goals. Conclusion We argue that if contemporary vocational education and training can be attractive to the young generation, the ideas expressed in Dewey's vocational aspect of education and Maslow's hierarchy of motivation should be considered by vocational education and training stakeholders when making vocational education career choice or goals.